To BEE or not to BEE? South Africa's 'Black Economic Empowerment' (BEE), corporate governance and the state in the South - Stefano Ponte; Simon Roberts; Lance van Sittert (Danish Institute for International Studies (DIIS), 2006)
Black Economic Empowerment (BEE) has been a major policy thrust of the democratic governments in South Africa since 1994 in attempting to redress the effects of apartheid. This paper explores the historical precedents to BEE in South Africa, its origins, and its points of contact with the experience of `empowerment' in Malaysia. The authors review the different steps taken by the South African government in promoting empowerment over the past 12 years, together with some of outcomes to date. They also draw from three case studies of sectors where government has different degrees of leverage over the process of BEE – industrial fisheries, metals and engineering, and wine. The paper highlights that the new `broad-based' configuration of BEE has become a managerial and technocratic process that may thwart the overall objectives of `empowerment' in at least four ways. First, it is moving the debate from a political terrain, where redistribution is in theory possible, to a managerial terrain, where discussions are technical and set within the limits of codification, measurement intervals and systemic performance. Second, by so doing, it is partially shifting the responsibility for promoting change and for bearing the consequences of failure away from elected government and towards a generic `system' that has a life of its own. An emerging industry of accountants, technocrats, auditors and certifiers are the foot soldiers of this system, but bear no responsibility. Third, BEE is now based on such levels of complexity that it implicitly legitimizes `outsourcing' of its management from government to the private (auditing) sector, thus reinforcing a further weakening of the state and facilitating a next round of `outsourcing' of previously political and now managerialized functions. Finally, BEE managerialism is forwarding the idea that (some level of) redistribution is actually possible in a neo-liberal economic policy setting, thus disenfranchising more radical options in policy-making.
Keywords: 330; Ethnische Diskriminierung; Rassenpolitik; Wirtschaftspolitik; Fischerei; Metallindustrie; Weinbau; Geschichte; Südafrika; Demokratisierung